2015
DOI: 10.5664/jcsm.5196
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Capabilities of Clinical Assessment, Diagnostic Criteria, and Polysomnography in Detecting Sleep Bruxism

Abstract: Presence of muscle fatigue and temporal headaches can be considered good tools to screen SB patients. None of the diagnostic criteria evaluated was able to accurately identify patients with SB. AASM criteria had the strongest diagnostic capabilities and--although they do not attain diagnostic values high enough to replace the current gold standard (PSG)--should be used as a screening tool to identify SB.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
63
1
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(70 citation statements)
references
References 16 publications
2
63
1
4
Order By: Relevance
“…В литературе отсутствуют ее общепринятые кри-терии [18]. По данным Международной классифика-ции нарушений сна 3-го издания, диагностические критерии для НБ следующие:…”
Section: диагностика бруксизмаunclassified
See 1 more Smart Citation
“…В литературе отсутствуют ее общепринятые кри-терии [18]. По данным Международной классифика-ции нарушений сна 3-го издания, диагностические критерии для НБ следующие:…”
Section: диагностика бруксизмаunclassified
“…• наличие регулярного, частого скрежета зубов во время сна; • наличие одного или нескольких следующих клинических признаков: -патологическая стираемость зубов, соот-ветствующая ранее упомянутым сообще-ниям о скрежете зубов во время сна; -преходящая утренняя усталость или боль жевательной мышцы; и / или височная го-ловная боль; и / или сжимание челюстей при пробуждении, соответствующие ранее упомянутым сообщениям о скрежете зубов во время сна [18][19][20]. В основном пациенты с бруксизмом узнают о нем случайно, когда их партнеры слышат ночной скрежет зубов и сообщают об этом.…”
Section: диагностика бруксизмаunclassified
“…1,10 O desgaste do dente pode não ser considerado como uma base confiável para o diagnóstico, uma vez que pode ser influenciado por vários fatores, como idade, gênero, dieta e outros hábitos parafuncionais. 11,12 Nos últimos anos, a etiologia multifatorial de desgaste dentário tem sido enfatizada, sendo que uma combinação de fatores mecânicos e químicos muitas vezes pode ser verificada, e hábitos parafuncionais são apenas um dos muitos fatores de risco. 12,13 Diante da relevância do tema, o objetivo deste estudo piloto foi identificar a prevalência de bruxismo em universitá-rios da Universidade Federal dos Vales do Jequitinhonha e Mucuri (UFVJM), no mês de julho de 2014.…”
Section: Prevalence and Factors Associated With Bruxism In Universityunclassified
“…11,12 Nos últimos anos, a etiologia multifatorial de desgaste dentário tem sido enfatizada, sendo que uma combinação de fatores mecânicos e químicos muitas vezes pode ser verificada, e hábitos parafuncionais são apenas um dos muitos fatores de risco. 12,13 Diante da relevância do tema, o objetivo deste estudo piloto foi identificar a prevalência de bruxismo em universitá-rios da Universidade Federal dos Vales do Jequitinhonha e Mucuri (UFVJM), no mês de julho de 2014. Também foram investigados os fatores etiológicos correlacionados com a ocorrência do bruxismo, prevalência de desgaste dentário e a relação entre bruxismo e sinais e sintomas de disfunções temporomandibulares.…”
Section: Prevalence and Factors Associated With Bruxism In Universityunclassified
“…Furthermore, self-reported and clinically based diagnoses of SB in TMD patients have unacceptably low levels of agreement. Most recently, a study examining the ability of a variety of signs and symptoms to predict the gold standard of PSG-based RDC/SB (18) concluded that none was able to identify those with SB accurately (37). Even the more strongly associated symptoms such as temporal headaches and muscle fatigue, all had positive predictive values below 30%, when properly adjusting for an estimated population prevalence of PSG-based RDC/SB of 10% or less (38) rather than the artificially constructed case–control sample RDC/SB prevalence rate of 50%.…”
Section: Introductionmentioning
confidence: 99%